(untitled) (Journal of the College of Basic Education, 2022)
Proceeding from the importance of fertility as a complex and intertwined process to which the survival of human society is linked, and reflects what society possesses of human resources, and paves the way for a realistic vision of how to overcome demographic, economic and social problems and overcome them, and then fertility is a mirror that reflects many demographic, economic, social and environmental variables prevailing in society , because it is the product of these variables affected by it and affected by it.